Origin and evolution of hydrothermal fluids in the Marshoun epithermal Pb–Zn–Cu (Ag) deposit, Tarom-Hashtjin metallogenic belt, NW Iran - Kouhestani, Hossein; Mokhtari, Mir Ali Asghar; Qin, Kezhang; Zhao, Junxing (Ore geology reviews, 2019)
[Display omitted] •The Marshoun deposit is an intermediate-sulfidation style of epithermal mineralization.•Microthermometric data indicates trapping of moderate- to high-temperature and moderate-salinity fluids.•Fluid boiling and mixing facilitated hydrothermal alteration and mineralization.•Stable isotopes suggest the ore–fluid system evolved from magmatic to meteoric.•Mineralization at Marshoun is related to late Eocene shallow magmatic–hydrothermal activity at THMB. The Marshoun epithermal Pb–Zn–Cu (Ag) deposit is located in the Tarom–Hashtjin metallogenic belt (THMB), northwest Iran. The epithermal base metal veins are mainly hosted in Eocene volcanic and volcaniclastic rocks of the Karaj Formation, and late Eocene pyroxene quartz monzodiorite. The mineralization process can be divided into five stages: (1) quartz-chalcopyrite-pyrite veins and breccias, (2) quartz (calcite)-sphalerite-galena ± chalcopyrite ± pyrite veins and breccias, (3) barren post-ore quartz veinlets, (4) barren post-ore calcite veinlets, and (5) supergene mineral assemblages. The primary metallic minerals are pyrite, chalcopyrite, sphalerite, and galena; gangue minerals are mainly quartz, calcite, sericite, and chlorite. The main wall-rock alteration is silicification, intermediate argillic, carbonate, and propylitic alteration. Microthermometric measurements of primary LV fluid inclusion assemblages in quartz and sphalerite indicate that the veins were mainly formed at temperatures between 173 and 285 °C from fluids with salinities between 3.4 and 6.3 wt% NaCl equiv. Coexisting LV, VL, and V inclusions in quartz and sphalerite provide evidence for boiling in ore-stage breccia and veins. Additionally, the occurrence of bladed calcite as well as plumose and colloform/crustiform banded quartz in the ore zones and the presence of hydrothermal breccias are consistent with boiling. Obtained oxygen and sulfur isotope compositions (δ18Owater = +9.2‰ to +1.5‰; δ34SH2S = –10.0‰ to –5.7‰) indicate there was a major contribution from a magmatic component to metallogenesis. The fluid inclusion and stable isotope data indicate that fluid boiling and mixing facilitated hydrothermal alteration and mineralization at Marshoun. The Marshoun deposit is interpreted as an intermediate-sulfidation style of epithermal mineralization. Our data suggest that the epithermal mineralization in the THMB are related to late Eocene (ca. 36–37 Ma) shallow magmatic–hydrothermal activity. The altered Eocene volcanic-subvolcanic rocks, particularly at the intersection of subvolcanic rocks with faults were the most favorable locus for exploration targeting of epithermal ores at THMB.